Normal incidence acoustic absorption characteristics of a carbon nanotube forest. (1st December 2017) - Ayub, M.; Zander, A.C.; Howard, C.Q.; Cazzolato, B.S.; Huang, D.M.; Shanov, V.N.; Alvarez, N.T.
Highlights: Acoustic absorption of vertically aligned CNT forests is investigated experimentally. A 3 mm CNT forest can provide up to 10% acoustic absorption within 125 Hz–4.2 kHz. Limitations of classical models to accurately predict absorption of CNTs are exposed. A CNT absorber of lower thickness and mass can achieve an absorption equivalent to a conventional material. A verification procedure for measurement of acoustical properties of small samples is reported. Abstract: The acoustic absorption of carbon nanotube (CNT) absorbers made of vertically aligned CNT forests is investigated experimentally in an impedance tube using the two-microphone method with normal incidence. Results show that a 3 mm thick forest of CNTs can provide up to 10 % acoustic absorption within the frequency range 125 Hz–4 kHz. Theoretical predictions of the acoustic absorption properties of CNTs made using classical acoustic theories, including the Biot-Allard and Johnson-Allard models, agree reasonably well with the experimental results in terms of the general trends, although there are significant difference at specific frequencies. This suggests that nanoscopic acoustic absorption mechanisms are important and are not accurately represented within the classical models developed for conventional porous materials. In addition, theoretical studies of the acoustic absorption potential of CNT forest indicate that they may provide better acoustic absorption than conventional porous materials of equivalent thickness and mass, and that the absorption could be enhanced significantly with a lower forest density of CNTs than the samples tested in this study.